Evaluation of AquaCrop model for optimal and deficit irrigation conditions on Phaseolus vulgaris - Norge Tornés Olivera (Universidad Central "Marta Abreu" de Las Villas, 2021)
The investigation was developed during the months of January until April of 2017, with the objective of evaluating the behavior of the pattern AquaCrop in the simulation of the agricultural yield of the dry bean crop under variables conditions of availability water. The investigation area belongs to the Cooperativa de Créditos y Servicios (CCS) Clemente Ramos, municipality of Bayamo, Granma province, which is located at the 20° 22' 57,1" of Latitude N and at 76° 38' 16,4" Longitude O, with a height of 52,50 msnm. A randomized experiment design was utilized, with three variants and three repetitions. The experimental variants were, mark of plantation of 0,07*0,7 m and 100 % of the evapotranspiration demand, mark of plantation of 0,07*0,7 m and 80 % of the evapotranspiration demand, mark of plantation of 0,05*0,55 m and 100 % of the evapotranspiration demand. The model simulated the canopy cover acceptably, when being achieved values of R2 (0,94; 0,94 and 0,92) and values of d (0,87; 0,77 and 0,73) for the three variants, while the values achieved in the simulation of air dry biomass under limitation conditions, alone they were acceptable the R2 0,99 and d 0,72 in the variant 1. The agricultural yield was simulated from an acceptable way when being achieved R2 98,88 and EAM 0,044.